Advancing Precision Medicine for Alcohol Use Disorder: Replication and Extension of Reward Drinking as a Predictor of Naltrexone Response. (11th September 2019) - Witkiewitz, Katie; Roos, Corey R.; Mann, Karl; Kranzler, Henry R.
Abstract : Background: Precision medicine aims to identify those patients who will benefit the most from specific treatments. Recent work found large effects of naltrexone among "reward drinkers, " defined as individuals who drink primarily for the rewarding effects of alcohol. This study sought to replicate and extend these recent findings by examining whether the desire to drink mediated the effect of naltrexone among reward drinkers. Methods: We conducted a secondary analysis of a 12‐week randomized clinical trial of daily or targeted naltrexone among problem drinkers ( n  = 163), with a focus on 86 individuals ( n  = 45 naltrexone and n  = 41 placebo) who received daily medication. Interactive voice response technology was used to collect daily reports of drinking and desire to drink. Factor mixture models were used to derive reward and relief phenotypes. Moderation analyses were used to evaluate naltrexone effects, with phenotype as a moderator variable. Multilevel mediation tested average desire to drink as a mediator. Results: Results indicated 4 phenotypes: low reward/low relief; low reward/high relief; high reward/low relief; and high reward/high relief. There was an interaction between the high reward/low relief subgroup ( n  = 10) and daily naltrexone versus placebo on drinks per drinking day (DPDD; p  =   0.03), percent heavy drinking days ( p  =   0.004), and daily drinking ( p  =   0.02). As compared to placebo, individuals in the high reward/low relief phenotype who received daily naltrexone had significantly fewer DPDD (Cohen's d  = 2.05) and had a lower proportion of heavy drinking days (Cohen's d  = 1.75). As hypothesized, reductions in average desire to drink mediated the effect of naltrexone on average daily drinking among the high reward/low relief drinkers (moderated mediation effect: p  =   0.029). Conclusions: This theory‐driven study replicates the empirical finding that naltrexone is particularly efficacious among high reward/low relief drinkers. Our study brings the field a step closer to the potential of using a precision medicine approach to treating alcohol use disorder. Abstract : In a post‐hoc precision medicine analysis of a 12‐week clinical trial, the current study examined the efficacy of naltrexone versus placebo for reward drinkers, individuals who drink primarily for the rewarding effects of alcohol and not for the relieving effects. As compared to placebo, reward drinkers who received naltrexone (50 mg/d) had significantly fewer drinks per drinking day (see Figure, Cohen's d  = 2.05). Reductions in average desire to drink mediated the effect of naltrexone on average daily drinking among reward drinkers.